‘STEM education and innovation are essential for national success’: A profile of Australia’s Chief Scientist, Ian Chubb - Head, Beverley (Journal of Telecommunications and the Digital Economy, 2014)
Beverley Head interviews Australia’s Chief Scientist, Professor Ian Chubb AC. This article plots his scientific and academic journey, and reveals his concerns regarding the need to boost Australia’s performance in science, technology, engineering and mathematics (STEM) in order to transform the national economy.